Analisis Pengaruh Kualitas Pelayanan terhadap Kepuasan Tinggi dan Rendah Nasabah di Bank Syari’ah Mandiri Cabang Salatiga - Wiyanto Wiyanto (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2016)
The purpose of this study was to test the effect of a variable quality of service with tangible, reliability, responsiveness, assurance and empathy on the high and low customer satisfaction at Syariah Mandiri Bank, Salatiga. The study used a sample of 150 students of the Faculty of Economics and Business Islam IAIN Salatiga. Multiple regression analysis was used to test hypotheses of the study after the classic assumption test and test validity and reliability. The results showed that the variable of reliability, responsiveness, and empathy effect on the high and low customer satisfaction Syariah Mandiri Bank with the branch in Salatiga. Furthermore, the quality of service with these five indicators affect the high and low customer satisfaction Syariah Mandiri Bank, Salatiga together.